Analytical Method for the Detection of Residual Active Ingredients Found in Neutralized Suspensions of Antimicrobial Products. (22nd November 2019) - Kamel, Alaa; Tomasino, Stephen F
Abstract: An analytical method for determining the presence and levels of residual active ingredients found in neutralized suspensions of phenolic and quaternary ammonium salt-based antimicrobial products was developed using solid-phase extraction in combination with LC-tandem MS. A single-laboratory validation of the method was performed at three concentration levels for the quaternary ammonium compounds (also referred to as benzalkonium chlorides or BACs) and the phenols in the presence of letheen broth neutralizerat 2.5 and 2.75 μg/mL, respectively, as well as at dilutions of 1:10 and 1:100 in those concentrations. The method's lowest LODs were 0.005 μg/g for BACs and 0.006 μg/g for phenols. The average recovery of the fortified samples for both active ingredients ranged between 80 and 124%, and RSDs were generally <20%. In a related study, the effectiveness of letheen broth with and without sodium thiosulfate was evaluated as a neutralizer for sodium hypochlorite. The results showed that letheen broth without sodium thiosulfate neutralizes chlorine concentrationsup to 60 ppm, and that 200 μg sodium thiosulfate are required to neutralize a 72 ppm concentrated chlorine solution in letheen broth.